1993
DOI: 10.1111/j.1365-2621.1993.tb09355.x
|View full text |Cite
|
Sign up to set email alerts
|

Flesh Quality in Snapper, Pagrcrs auratus, Affected by Capture Stress

Abstract: Muscle metabolites in resting, tank acclimated snapper, Pums aurafus, were monitored for 72 hr postmortem and compared with values from exercised or commercially caught fish. The physiological status of the live animal was quantified by plasma cortisol and blood chemistry. Cortisol levels were lowest in unstressed controls (6.8rt2.1 ng mL-r) while exercised laboratory fish had highest levels (67.7~ 11.2 ng mL-t). Control fish maintained a constant K-value for 72 hr in chilled storage; all other groups had sign… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

6
90
1
2

Year Published

1999
1999
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 136 publications
(99 citation statements)
references
References 23 publications
6
90
1
2
Order By: Relevance
“…Ling & Wells 1985b;Bollard et al 1993;Lowe & Wells 1996). This research confirmed that, as in the laboratory, the primary stress response of fish to angling/handling involved sequential increases of catecholamines and then corticosteroids (Lowe et al 1993;Lowe & Wells 1996), serving to modulate the metabolite status, the blood oxygen carrying capacity, blood viscosity and even cell maintenance function of fish to satisfy and protect against the sudden increase in energy demand (Ling & Wells 1985b;Lowe et al 1993;Ryan et al 1995;Lowe & Wells 1996). Of particular interest are the manipulative experiments of Bollard et al (1993) that artificially raised plasma cortisol levels in snapper and showed, for the first time, that cortisol in fish retains lactate in circulation which, through follow-up research, is now believed to be a mechanism providing metabolic fuel postexercise (Eros & Milligan 1996).…”
Section: Reproductive Behavioursupporting
confidence: 72%
See 1 more Smart Citation
“…Ling & Wells 1985b;Bollard et al 1993;Lowe & Wells 1996). This research confirmed that, as in the laboratory, the primary stress response of fish to angling/handling involved sequential increases of catecholamines and then corticosteroids (Lowe et al 1993;Lowe & Wells 1996), serving to modulate the metabolite status, the blood oxygen carrying capacity, blood viscosity and even cell maintenance function of fish to satisfy and protect against the sudden increase in energy demand (Ling & Wells 1985b;Lowe et al 1993;Ryan et al 1995;Lowe & Wells 1996). Of particular interest are the manipulative experiments of Bollard et al (1993) that artificially raised plasma cortisol levels in snapper and showed, for the first time, that cortisol in fish retains lactate in circulation which, through follow-up research, is now believed to be a mechanism providing metabolic fuel postexercise (Eros & Milligan 1996).…”
Section: Reproductive Behavioursupporting
confidence: 72%
“…The metabolic response of fish to handling and capture stress Energy is the fundamental currency of life, so the impact of stress on the subsequent day-to-day activity of fish (or even flesh quality of angled fish) is influenced strongly by the manner in which useable energy (adenosine triphosphate [ATP]) is created and consumed through aerobic and anaerobic metabolic pathways (Wells 1987;Lowe et al 1993). The coastal waters around Leigh are host to a wealth of sport fishes, so the early efforts of physiologists at the Leigh Laboratory were dedicated to understanding the metabolic effect of stress from line capture and associated handling (Ling & Wells 1985a, b;Wells 1987).…”
Section: Reproductive Behaviourmentioning
confidence: 99%
“…The stress responsiveness of turkeys (Meleagris gallopavo; Brown and Nestor, 1973), chickens (Gallus domesticus; Gross and Siegel, 1985) and the Japanese quail (Coturnix coturnix japonica; Satterlee and Johnson, 1988) have been modified by selective breeding strategies, with varying degrees of success. A similar approach has been considered with respect to aquacultured fish in which frequent or prolonged exposure to stressors significantly and adversely affects growth (Pickering, 1993;Pankhurst and Van Der Kraak, 1997), reproductive performance (Pickering et al, 1987a;Campbell et al, 1992Campbell et al, , 1994, the immune system (Balm, 1997) and flesh quality (Lowe et al, 1993;Sigholt et al, 1997). It is argued that in an environment in which stressful stimuli are frequent or prolonged, fish which possess a low level of responsiveness to stress will be less severely affected than fish displaying a more pronounced reactivity to stress (Pottinger and Pickering, 1997).…”
Section: Introductionmentioning
confidence: 99%
“…Stress at death affects the quality and freshness during shelf life, with the consequent variation of parameters during storage, such as rigor release, ATP catabolites evolution and general aspects of the fish (Pottinger 2001;Tejada et al 2001;Poli et al 2005). These changes are widely considered as good indicators to evaluate the stress degree and the quality changes both in terrestrial species such as pigs (Warris et al 2003) and in fish (Lowe et al 1993;Marx et al 1997;Robb and Warriss 1997;Poli et al 2005).…”
Section: Introductionmentioning
confidence: 99%